Improving Recovery and Outcomes Every Day after the ICU (IMPROVE): study protocol for a randomized controlled trial - Sophia Wang; Jessica Hammes; Sikandar Khan; Sujuan Gao; Amanda Harrawood; Stephanie Martinez; Lyndsi Moser; Anthony Perkins; Frederick W. Unverzagt; Daniel O. Clark; Malaz Boustani; Babar Khan (Trials, 2018)
Abstract Background Delirium affects nearly 70% of older adults hospitalized in the intensive care unit (ICU), and many of those will be left with persistent cognitive impairment or dementia. There are no effective and scalable recovery models to remediate ICU-acquired cognitive impairment and its attendant elevated risk for dementia or Alzheimer disease (AD). The Improving Recovery and Outcomes Every Day after the ICU (IMPROVE) trial is an ongoing clinical trial which evaluates the efficacy of a combined physical exercise and cognitive training on cognitive function among ICU survivors 50 years and older who experienced delirium during an ICU stay. This article describes the study protocol for IMPROVE. Methods IMPROVE is a four-arm, randomized controlled trial. Subjects will be randomized to one of four arms: cognitive training and physical exercise; cognitive control and physical exercise; cognitive training and physical exercise control; and cognitive control and physical exercise control. Facilitators administer the physical exercise and exercise control interventions in individual and small group formats by using Internet-enabled videoconference. Cognitive training and control interventions are also facilitator led using Posit Science, Inc. online modules delivered in individual and small group format directly into the participants’ homes. Subjects complete cognitive assessment, mood questionnaires, physical performance batteries, and quality of life scales at baseline, 3, and 6 months. Blood samples will also be taken at baseline and 3 months to measure pro-inflammatory cytokines and acute-phase reactants; neurotrophic factors; and markers of glial dysfunction and astrocyte activation. Discussion This study is the first clinical trial to examine the efficacy of combined physical and cognitive exercise on cognitive function in older ICU survivors with delirium. The results will provide information about potential synergistic effects of a combined intervention on a range of outcomes and mechanisms of action. Trial registration ClinicalTrials.gov, NCT03095417. Registered on 23 March 2017. Last updated on 15 May 2017.